The Greek-Latin Dispute Over the Communion of Infants - Salij, Jacek (Studia Theologica Varsaviensia, 2020)
$. e Greek-Latin dispute over the communion of infants is an integral part of the dispute over Eucharistic worship. e reason for the dispute are the changes in the western liturgy as a result of the reaction against Berengar. e changes themselves were based on drawing consequences from the traditional Eucharistic realism, but they are a novelty in relation to specific traditional customs. us, Orthodox theology accused the West of illegitimate novelty in relation to traditional rites, while Catholic theology justified the changes with fidelity to the traditional worship of the Blessed Sacrament. Both approaches reflect two different approaches to ecclesiastical tradition. In the East, more attention is paid to the permanence of the deposit received, while in the West, the need for the organic development of tradition is appreciated. +. In addition, the dispute revealed separate positions on the necessity of the Eucharist for salvation. Some emphasised the sacramentum, while others emphasised res. Eastern theology taught about the necessity of material consumption of the Eucharist, and Simeon of essaloniki or Gregory Dattivensis even claimed that anyone who has never consumed the Eucharist can never be saved. Western theology, on the other hand, emphasised that already through baptism man really becomes a member of the Body of Christ. %. e dispute revealed the different links between the theology of the Eucharist and theology of grace. e Eastern followers of infant communion saw in the Eucharist, above all, the food of a new creation, food for eternal life. Defenders of the Western custom emphasised that infants are free from temptation, so they do not need the help of the Eucharist in the fight against evil. e first theology links the Eucharist rather with the grace of holiness, the second with the grace of works. *. e diversity of liturgical disciplines is also reflected in pastoral ministry. In the churches that administer all three sacraments of initiation to infants, there is less awareness that anyone, not only a priest, can baptise someone in life-threatening circumstancs. ?. e original attitude towards the other party’s otherness was characterised by aggressive reluctance on both sides. However, the allegation of a deviation from the truth appeared only in Eastern theology. is is not some particular merit of Western theology but is due to objective reasons. Western theology, by its very nature, could not sharply stigmatise a custom, the tradition of which was indisputable. 3. At the Florentine Council, which clearly distinguished heresies from legitimate differences, the communion of infants was placed on the list of the latter. However, as the Florentine solutions were not widely accepted, they increased the original diversity of positions. In the Orthodox Church, it is still generally considered dogmatically unacceptable not to grant communion to infants. e position of Orthodox theology has become established especially during anti-Uniate polemics. In the Western Church, on the other hand, the admissibility of the Eastern custom is now clearly proclaimed, however, quite o;en its own custom is considered to be more appropriate. is teaching was officially confirmed by the Council of Trent. 0. Uniate theology, in defending the legitimacy of Western custom, basically uses classical Western argumentation, which sees in the Eucharist above all the source of works and graces. 5. In the post-reform period, especially in the polemic a;er the Brest Union, Catholics of both rites o;en invoke the communion of infants as a testimony to the legitimacy of communion in one form. 4. e Uniate opponents of the Latinisation of the union most o;en did not take a clear position on the western influences on the Eucharistic spirituality of the Uniate Churches. e subject of their criticisms were, by their very nature, those manifestations of Latinisation which have no connection with dogma. e silence about transformations in Eucharistic spirituality expressed rather the conviction that these changes were correct. Partly, however, it could have been tactical silence. History also knows of the silence caused by the disregard for theology, which was replaced by official orders and repressions during the liquidation of the union. $@. Using the example of the communion of infants, the difficulty of carrying out a strict borderline between the catholicisation and the Latinisation of the Eastern liturgy is revealed. With regard to Eucharistic customs, this distinction depends on the extent to which the doctrine of concomitance and the liturgical consequences drawn from it in the Western Church belong to the essence of Catholicism, and to what extent they are only a specific feature of Western spirituality. Traditionally, the first alternative was rather accepted, but in the twentieth century there were opinions in favour of a second solution.